Servidores com deficiência de instituições públicas de ensino superior e a pandemia da Covid-19 - Simone Gonzaga França Oscar (2021)
For a long time, people with disabilities were excluded from social life and prevented from performing different occupations. In the course of history, they were segregated, integrated and were only included after the emergence of different social movements related to human rights. Although inclusion policies have been proposed, legislation is still needed to ensure all the real guarantees of opportunities for inclusion in different contexts. Therefore, there are still difficulties to be overcome for the inclusion of everyone. In relation to the labor market, people with disabilities may face difficulties in the process of admission, adaptation and permanence in employment.The same is observed with regard to architectural and urban accessibility, transportation, communication and information.The aim of this study was to describe the process of admission and monitoring of employees with disabilities in public institutions of higher education.Specifically, we sought to identify the demands and problems related to the activities carried out by these servers, and describe the accessibility and types of barriers that exist in a typical workday in the face-to-face and remote period established in the Covid-19 pandemic.In Minas Gerais there are eleven public universities. All of them were contacted and five became partners in this study.The federal public employee of these institutions were sent an electronic invitation containing the formalization for participation and the period for the videoconference. It was used for the online interviews a script with open questions, the Brazil Economic Classification Criteria and the Canadian Occupational Performance Measure. The interviews were recorded, transcribed and submitted to thematic categorical content analysis.The results show a reduced number of employees with disabilities in the institutions, reveal attitudinal, architectural and communication/information barriers, as well as the accessibility of co-workers, and show flaws in the admission and monitoring process of most employees with disabilities in the institutions. The set of information on the subject can help universities improve the process of welcoming and adapting servers with disabilities, as well as assisting in the development of strategies for the inclusion of everyone in the university environment.